Zur Literarkritik und Redaktionsgeschichte der alttestamentlichen Josefserzählung - Röhrig, Meike 1990-; Ede, Franziska 1977- (2018)
This article is a review of and discussion with Franziska Ede's Book on the Joseph story (BZAW 485). The main idea of Ede's book is that Gen 37-50 can best be explained by means of a Fortschreibungsmodell rather than with a source model. The approach offers many insightful explanations and succeeds to explain large parts of the Joseph story as a result of innerbiblical interpretation. The other main thesis of the book claiming a pre-priestly connection of the patriarchal stories and the exodus account did, on the contrary, not withstand a critical assessment.
Keywords: Josefserzählung; Rezension